Data mining application on students' data - BULDU, ALİ (ELSEVIER SCIENCE BV, 2010)
In today's world, due to the rapid development of technology, the amount of data stored has been constantly increasing in every field. It is intended to obtain meaningful, valuable information that is not previously known from these data by applying data mining techniques. In data mining techniques, association rules are one of the most preferred techniques. Apriori algorithm is the most used one in these association rules. In this work, by being carried out apriori algorithm upon the data of students of Istanbul Eyup I.M.K.B. Vocational Commerce High School, the rules have been produced and from the results obtained the relation between the courses that the students failed have been revealed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Data mining; education; association-relation rule; apriori algorithm; data reducing